Звіти чернігівських архієреїв ХІХ – початку ХХ ст. як історичне джерело - Тарасенко, О. (Сiверянський лiтопис, 2015)
Стаття присвячена актуальній темі в історичній науці, зокрема, в джерелознавстві. Звіти чернігівських архієреїв, накопичені в період з 1847 р. по 1916 р., досі не були предметом спеціального дослідження і не впроваджені до наукового обігу. Метою дослідження є з’ясування законодавчої бази та історичних умов для появи та тривалого існування цього виду масової документації, встановлення ступеню збереженості звітів чернігівських владик про становище єпархії, проаналізування звітів на предмет повноти, інформативності, репрезентативності, верифікованості та джерельної цінності. Статья посвящена актуальной проблеме в исторической науке, в частности, в
источниковедении. Отчеты черниговских архиереев, накопленные в период с 1847 г.
по 1916 г., до сих пор не стали предметом специального исследования и не введены
в научный оборот. Целью исследования является изучение законодательной базы и
исторических условий для появления и длительного существования этого вида массовой документации, определение степени сохранности отчетов черниговских владык о состоянии епархии, проанализирование отчетов на предмет полноты, информативности, репрезентативности, верификованости и источниковой ценности. The article is devoted an actual theme in historical science, in particular. Reports of the
Chernihiv bishops, accumulated in a period from 1847 to on 1916, until now were not the article
of the special research and not inculcated to the scientific circulation. A research purpose is
finding out of legislative base and historical situation for appearance and protracted existence
of this type of mass document, establishment of degree of stored of reports of the Chernihiv
bishops, about position of diocese, to analyse reports for the purpose plenitude, informing,
presentable, objectivity and a spring value.
Reports on position of the Chernihiv diocese are a source many-sided, presentable which
contains various information on church religious life in a region. Evaluation descriptions of
guidance of diocese (real or imaginary) densely accompanied with the richest actual material.
Statistical materials of reports represent composition of diocese, change in the organs of
management, amount of churches, monasteries, schools of church, quantity of congregation
and clergy, their morally religious mood and educationally professional level. In reports the
represented facts of opening/closing of monasteries, churches, building, re-erecting, repairs,
sourcing. Valuable is also material, which touches activity of parochial and diocese care,
spiritual schools and seminary, fraternities and other diocese establishments and organizations.
The important feature of reports consists in that they engulf a considerable period (1847 –
1916), that characterized as a source of mass origin. It enables a researcher to use them for the
study of history of the Chernihiv diocese in a dynamics, on the different stages of development
and on the whole during the second half XIX – to beginning of XX century.